From Coronaries to Cirrhosis: The Role of Percutaneous Coronary Intervention and Dual Antiplatelet Therapy in End-Stage Liver Disease - Taylor C. Remillard MD; Don C. Rockey MD (SAGE Publishing, 2021)
Drug-eluting stents (DES) have superior efficacy compared with bare metal stents (BMS) for treatment of coronary artery lesions. However, BMS continue to play an important role in percutaneous coronary intervention for patients who are at a high bleeding risk, because they require a shorter duration of dual antiplatelet therapy. However, new developments in DES and understanding of the optimal time required for dual antiplatelet therapy after percutaneous coronary intervention may further limit the use of BMS. Furthermore, the use of dual antiplatelet therapy is complicated in patients with cirrhosis, who may have coagulopathy. In this article, we present the case of a patient with cirrhosis and end-stage chronic liver disease with coronary artery disease and a proximal left anterior descending stenosis who received a DES and had multiple episodes of gastrointestinal bleeding. We review the literature addressing DES and BMS in patients at high risk of bleeding. We also review the optimal duration of dual antiplatelet therapy.